The Effect of Fixed Asset Accounting System, Internal Control System on the Quality of Financial Statements of the Regional Government of Sungai Penuh City - Irennia, Dina; Sam, Iskandar; Erwati, Misni (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine“the effect of the fixed asset accounting system and internal control system on the quality of local government financial statements. The population in this”study consists of 30 regional government agencies (OPD), with a sample of 72 individuals from these 30 agencies, selected using the purposive sampling method. This research is quantitative in nature, using primary data. The data were processed using IBM SPSS Statistics 29. The data analysis technique employed is multiple linear regression analysis. The results indicate that the fixed asset accountingsystemand internal control system significantly affects the quality of financial statements. Additionally, according to the study, the internal control system and fixed asset accounting system both significantly affect the quality of financial statements”at the same time.